Interrupting the Conspiracy of Silence: Historical Trauma and the Experiences of Hmong American Women - (:unkn) unknown (My University, 2015)
The Hmong have endured a history of oppressive and traumatic experiences. The Secret War was particularly significant as it resulted in genocide, dislocation, and oppression for the Hmong. In addition, the Hmong experience and their involvement as U.S. allies remained largely a secret for several decades. Current research suggests that Hmong Americans experience a high prevalence of mental health issues including depression, anxiety, and substance abuse as well as other health disparities. The purpose of this project was to explore how a history of massive group trauma and secrecy maintained about the Hmong may contribute to the current conditions of Hmong Americans. This qualitative project applied the conceptual frameworks of intergenerational transmission of historical trauma (Trauma and the Continuity of Self: A Multidimensional, Multidisciplinary Integrative Framework) and the conspiracy of silence to explore the experiences of Hmong American women. In addition, this project explored the impact of a psychosocio-educational intervention based on the Cultural Context Model. Specifically, this study posed the following research questions: 1. What, if any, are the experiences of Hmong women in relation to intergenerational historical trauma? 2. What, if any, are Hmong women’s experiences of the conspiracy of silence in relation to Hmong historical trauma? 3. What, if at all, is the impact of a psychosocio-educational intervention on historical trauma for Hmong women? Nine Hmong American women were recruited for this project and completed initial interviews, a psychosocio-educational intervention, and post-intervention interviews. This project revealed that participants described experiences congruent with the construct of historical trauma and the conspiracy of silence. In addition, findings indicate that following a psychosocio-educational intervention, participants experienced consciousness-raising of societal and historical factors; experienced catharsis, unresolved grief, appreciation, and empowerment; and demonstrated further integration of their identity structures. This project offers insight into Hmong historical trauma and suggests interrupting the conspiracy of silence as a catalyst for healing and liberation for Hmong Americans. Further discussion of findings, implications, limitations, and future directions are considered.
Keywords: Conspiracy of Silence; Cultural Context Model; Historical Trauma; Hmong; Mental Health; Women